Operation and control of three phase microgrids consisting of single-phase DERs - Chandrasensa, Ruwan; Shahnia, Farhad; Rajakaruna, Sumedha; Ghosh, A. (IEEE, 2013)
Autonomous operation of a three-phase microgrid (MG) consisting of arbitrarily located single-phase distributed energy resources (DER) among the three phases is investigated. Due to random connection of single-phase loads and DERs to different phases, it is highly probable that one phase has more generation while another phase has more demand. This becomes a challenging issue during autonomous operation. This paper demonstrates how single-phase DERs in one phase can share the load demand in other phases. Several case studies are carried out using PSCAD/EMTDC to demonstrate the efficacy of the proposed power management and control strategy for single-phase DER converters distributed unequally among the three-phases in the MG.